Fast Facts from the 2018 Mozambique MIS - The DHS Program (2018)
The 2018 Mozambique Malaria Indicator Survey (IIM) provides population-based estimates on malaria indicators to inform strategic planning and program evaluation. The 2018 LMIS is the 6th survey to be conducted in Mozambique through The DHS Program.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde